2023
DOI: 10.1177/22799036231181716
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive coronary flow velocity reserve assessment predicts adverse outcome in women with unstable angina without obstructive coronary artery stenosis

Abstract: Background: Evaluation of coronary flow velocity reserve (CFVR) is the physiological approach to assess the severity of coronary stenosis and microvascular dysfunction. Impaired CFVR occurs frequently in women with suspected or known coronary artery disease. The aim of this study was to assess the role of CFVR to predict long-term cardiovascular event rate in women with unstable angina (UA) without obstructive coronary artery stenosis. Methods: CFVR in left anterior descending coronary artery was assessed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It was previously shown to have a prognostic value for cardiovascular events in different systemic diseases. [6][7][8] Transthoracic echocardiography can be used to measure CFR; it is preferred because of its high diagnostic accuracy, versatility, low cost, and especially not being exposed to radiation. 9 Although conventional atherogenic lipid parameters are used to assess the risk of CAD, many extensive epidemiological studies revealed that novel lipid indices, such as the plasma atherogenic index (PAI), have better predictive value for atherosclerotic CAD risk assessment than conventional ones.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown to have a prognostic value for cardiovascular events in different systemic diseases. [6][7][8] Transthoracic echocardiography can be used to measure CFR; it is preferred because of its high diagnostic accuracy, versatility, low cost, and especially not being exposed to radiation. 9 Although conventional atherogenic lipid parameters are used to assess the risk of CAD, many extensive epidemiological studies revealed that novel lipid indices, such as the plasma atherogenic index (PAI), have better predictive value for atherosclerotic CAD risk assessment than conventional ones.…”
Section: Introductionmentioning
confidence: 99%